Prognostic Value of Ambulatory Blood Pressure in the Obese: The Ambulatory Blood Pressure‐International Study. Issue 2 (5th October 2015) - Palatini, Paolo; Reboldi, Gianpaolo; Beilin, Lawrence J.; Casiglia, Edoardo; Eguchi, Kazuo; Imai, Yutaka; Kario, Kazuomi; Ohkubo, Takayoshi; Pierdomenico, Sante D.; Schwartz, Joseph E.; Wing, Lindon; Verdecchia, Paolo
Abstract : The purpose of this study was to compare the predictive value of ambulatory blood pressure (BP) vs office BP for cardiovascular events during a 5.8‐year follow‐up period in the obese and nonobese participants of the Ambulatory Blood Pressure‐International Study (n=10, 817). Both ambulatory BP and office BP considered separately were predictive of cardiovascular events. However, in Cox models including both pressures, only ambulatory BP was associated with outcome. Among obese patients, the hazard ratios for a 10‐mm Hg increase in 24‐hour and office systolic BPs were 1.37 (95% confidence interval, 1.20–1.53) and 0.91 (95% confidence interval, 0.76–1.07), respectively. Among nonobese patients, the corresponding hazard ratios were 1.39 (95% confidence interval, 1.31–1.47) and 0.94 (95% confidence interval, 0.88–1.00) ( P =not significant vs obese). Similar results were obtained for diastolic BP and for daytime and nighttime BPs. Ambulatory BP has similar predictive capacity in obese and nonobese patients, suggesting that ambulatory BP monitoring is a useful diagnostic tool for the assessment of obese individuals.